Increasing Student Expenses on Course Materials: The Cost Inefficiencies of Equitable Access - Clifford, Maryanne; Simon, Nicolas P. (Critical Education, 2025)
The high and ever-rising cost of college textbooks is a significant financial burden for students and their families, hindering access to essential learning materials and affecting academic performance and retention rates. To address these issues, instructors and universities are exploring cost-control methods such as free source materials, Open Educational Resources (OER), and automatic textbook billing (ATB) for affordable materials. This study analyzes the impact of automatic textbook billing, more specifically Equitable Access at one institution, examining potential savings for students. However, findings suggest that Equitable Access does not benefit most students financially. It disproportionately benefits students in higher-paying majors with expensive textbooks, subsidized by those in lower-paying majors with cheaper textbooks, raising equity concerns. This issue is particularly significant for students of color, who are more likely to graduate from lower-paying majors, bearing an undue financial burden.